Análisis del proceso de atención de pacientes y diseño de un modelo de optimización del servicio de atención del Centro Médico, Entorno y Compañía, Ltda., en la ciudad de Bogotá, D.C. (2019)
In the present project, an optimization model was carried out for the reduction in customer service times at the Entorno y Compañía Medical Center, LTDA. This analysis was carried out through the implementation of tools such as PESTAL, the analysis of Porter's five forces, the SWOT matrix, which allowed to know the current state of the Medical Center, with respect to its sector, and to establish strategies that would allow developing an optimization model to fulfill the objective of the project. The technical study was carried out in such a way that the current processes and the current management of the Medical Center are identified, in order to develop an action plan, where an amount of money was invested, to help comply with the model of optimization. Finally, the administrative and environmental issues of the Medical Center are analyzed, as well as the financial study, to know if the project can be executed and is viable.